PMP exam prep : all the help you need, from start to finish : video training for the PMP certification exam - Baca, Claudia (LiveLessons (Indianapolis, Ind.), 2008)
When it comes to passing the PMP certification exam, you’ll find no better resource than the PMP Exam Prep LiveLesson s. Not only do you get video-based tutorials from one of the nation’s leading PMP instructors, Claudia M. Baca, but you can also take an online practice exam up to five times before you take the real exam. Following the PMI’s curricula, the PMP Exam Prep LiveLessonshas everything you need to know to pass the PMP certification exam. Not only will you learn how to prepare for the exam, you will also get useful tips for completing and filing your paperwork, and discover useful things you should do on test day. Everything’s taught visually, using realistic project scenarios. You’ll master project initiation, planning, scoping, scheduling, budgeting, execution, monitoring and control, closing, quality, communications, procurement, PMI’s professional/social responsibility rules, and more.